2021
DOI: 10.3389/fmed.2021.688105
|View full text |Cite
|
Sign up to set email alerts
|

PTEN Hamartoma Tumor Syndrome: Skin Manifestations and Insights Into Their Molecular Pathogenesis

Abstract: Germline PTEN pathogenic variants cause a spectrum of disorders collectively labeled PTEN Hamartoma Tumor Syndrome (PHTS) and featured by hamartomas, developmental anomalies and increased cancer risk. Studies on experimental models provided evidence that PTEN is a “haploinsufficient” tumor-suppressor gene, however, mechanisms involved in the pathogenesis of clinical manifestations in PHTS patients remain elusive. Beyond analyzing clinical and molecular features of a series of 20 Italian PHTS patients, we perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The authors suggested that the presence of these features should prompt physicians and dentists to consider a further assessment for PHTS in adults [74]. These findings were supported by an Italian study of 20 patients with PTHS (16 adults and 4 children) wherein all patients had the typical mucocutaneous features of papules on the trunk or extremities (74%), papules in the oral mucosa (68%), facial papules (58%), and acral/palmoplantar keratosis (58%) [75,76].…”
Section: Pten Hamartoma Tumor Syndromementioning
confidence: 80%
“…The authors suggested that the presence of these features should prompt physicians and dentists to consider a further assessment for PHTS in adults [74]. These findings were supported by an Italian study of 20 patients with PTHS (16 adults and 4 children) wherein all patients had the typical mucocutaneous features of papules on the trunk or extremities (74%), papules in the oral mucosa (68%), facial papules (58%), and acral/palmoplantar keratosis (58%) [75,76].…”
Section: Pten Hamartoma Tumor Syndromementioning
confidence: 80%
“…More recently, Innella and colleagues identified an atypical mole/melanoma syndrome phenotype in patients with pathogenic PTEN variants containing a rare truncating mutation (c.495G>A) in the CDH13 gene (Innella et al 2021). Lifetime risk for acquiring melanoma is estimated at 6% (Tan et al 2012), which is substantially less than the estimated risk for breast, thyroid, endometrial, colorectal, and kidney carcinomas.…”
Section: Phosphatase and Tensin Homolog (Pten)mentioning
confidence: 99%
“…PTEN loss manifests as a complex spectrum of disorders called PTEN hamartoma tumor syndrome (PHTS) ( Innella et al., 2021 ). Patients with PHTS will primarily exhibit numerous hamartomas and a high risk of multisystem tumor development, although they may suffer from rarer genetic disorders such as Cowden syndrome (CS), Lhermitte‒Duclos disease, Bannayan‒Riley‒Ruvalcaba syndrome, and autism spectrum disorders ( Pilarski, 2019 ) ( Table 1 ).…”
Section: Defined Mixed-tumor Syndromes With Increased Melanoma Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the recommendations by genetic professionals, the pathways leading to PHTS diagnosis are difficult and highly variable (National Comprehensive Cancer Network [NCCN], http://www.nccn.org). Multiple unique pathognomonic features in PHTS have been reported, such as adult LDD, various mucocutaneous features, such as trichilemmomas, acral keratoses, papillomatous papules, multiple palmoplantar keratoses, macular pigmentation of glans penis (freckling on the glans penis), and esophageal glycogenic acanthosis (Innella et al, 2021; McGarrity et al, 2003; Morgan et al, 2022; Tan et al, 2011). Most of these unique pathologies are indolent, the appearance becomes more obvious after young adulthood, and cannot be easily recognized by health‐care providers (D'Ermo & Genuardi, 2022; Macken et al, 2019).…”
Section: Background and Introductionmentioning
confidence: 99%